Analisis Efisiensi Penggunaan Energi Listrik Sektor Rumah Tangga Di Pekanbaru Menggunakan Perangkat Lunak LEAP - Muhammad Sholeh; Firdaus Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Households are one sector of the country with 23% energy consumption of total energy in all sectors. In the household there are many electronic devices that consume electricity. This resulted in energy consumption among households to be very wasteful. For that action is required to minimize the consumption of household electrical energy. There are several ways that can be done to overcome this problem, one of which is to conduct a conservation energy audit. This audit is done using LEAP software. The conservation energy audit process is divided into 3 sections, i.e. energy surveys, initial energy audits, and detailed energy audits. The result of conservation energy audits undertaken include loads of 450, 900, 1300 and 2200 KWh. Finally the conclusion of the overall conservation energy audit is shown as follow, there was a 23% decrease in electricity consumption at 450 kWh load, 25% at 900 KWh load, 17% at 1300 KWh load and 20% at 2200 KWh load. from the test result that has been done, the reduction of annual cost is Rp 63,504 at the load of 450 KWh, Rp 110,538 at the load of 900 KWh, Rp 302.259 at 1300 KWh load and Rp 328,773 at the load of 2200 KWh. This proves that conservation energy audits can help reduce excessive energy consumption levelsKeywords: Energy Audits, Electricity Consumption, Household, LEAP